Analisis Pelanggaran Nilai-Nilai Kepemilikan Komunal Atas Rendang Minang Akibat Adanya Produk Rendang Babi: Analysis of Communal Possession Values Violations on Rendang Minang as an Effect of Rendang Babi Products - M Kahfi; Simona Bustani (Reformasi Hukum Trisakti, 2024)
Public knowledge about Intellectual Property Rights is currently lacking, especially with regard to the right of Communal Intellectual Property. One type of communal intellectual property that is not widely known by society is the Indication of Origin. The latest case related to Indication of Origin that has become a polemic is the case of the sale of Rendang Babi products at a Padang Restaurant in Jakarta. Rendang Babi doesn't measure up to the values of Minangkabau Society as the original proprietor of Rendang Minang. The issue that the author discussed in this case is whether Rendang Babi is a violation of the communal property values of Indication of Origin Rendang Minang and how to protect Communal Intellectual Property right of Rendang Minang according to the act. Based on analysis by the author that the Rendang Minang has the values embodied in it, namely cultural values, customs, religion (kehalalan), precision, and togetherness. Rendang gives an impression on the cultural identity of the Minangkabau based on Islamic Wisdom. The existence of a Rendang Babi was not thought to match the meanings contained in the Rendang. Thus, Rendang Babi product violates the communal possession value of the Rendang Minang.